Beyondsoft IPO (B) - Jia, Ning, (SAGE knowledge. Cases., 2016)
After 12 years of organic development, Beyondsoft Corporation has become a leading software outsourcing service provider in China in 2007. In a new round of financing, listing and industrial consolidation, Beyondsoft established overseas red-chip architecture, introduced foreign venture capitals and was well prepared for the listing in the U.S. However, when Beyondsoft filed a listing application to the U.S. Securities and Exchange Commission, a global financial crisis arrived unexpectedly and devastated the booming U.S. capital market, resulting in an ambiguous future for the good listing opportunity. Should the company wait for the next listing opportunity, or turn to other overseas markets, or go back to the domestic A-share market? President Ben Wang fell into a dilemma of multiple choices. This case study answers these questions.